(untitled) (International Journal of Banking and Finance, 2006)
This paper explores the definition of predictability of Warsaw Stock Index returns by using measures elaborated in Shannon-Mazur’s cybernetic information theory, potentially a new approach to understand capital market informational efficiency. The main message of this research is that the use of information theory methods may shed new light on the applicability of weak-form efficiency tests and the phenomenon of return unpredictability. Cybernetic interpretation in answering the question about market returns predictability and, in retrospect, may contribute to the discussion on the predictability tests of market returns.